Revitalisasi Profil Pelajar Pancasila: Peran Guru Pendidikan Agama Islam di SMP Negeri 1 Ngoro Jombang - Sa’diyah, Linda Halimatus; Umardiyah, Fitri (ALSYS, 2025)
Strengthening the Pancasila Student Profile is a strategic effort to shape students’ character in terms of faith, piety, global diversity, independence, critical thinking, creativity, and collaboration. This research is motivated by the significant role of Islamic Religious Education (IRE) teachers in internalizing these values into learning activities. The aim of this study is to explore and describe the role of IRE teachers in revitalizing the Pancasila Student Profile in grade VII of SMP Negeri 1 Ngoro Jombang. This research employs a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation from both primary and secondary sources. The results reveal that IRE teachers play a crucial role in integrating Islamic and Pancasila values into a holistic learning process. Teachers act as facilitators, motivators, evaluators, and role models in shaping student character. Project-Based Learning is found to be effective in contextually strengthening these character values. The study concludes that IRE teachers are key agents in fostering student character aligned with the Pancasila Student Profile. The implication of this study suggests the need for continuous professional development and institutional support to ensure effective implementation of these values in classroom settings.